2015
DOI: 10.1002/jsfa.7520
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of lutein in corn distillers dried grains with solubles relative to lutein in corn gluten meal based on lutein retention in egg yolk

Abstract: The results of the present experiment indicate that the DDGS can be a potential ingredient for laying hens to improve egg yolk colour and lutein concentrations of egg yolk although lutein in DDGS is less bioavailable than lutein in CGM. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Maize is one of the most important ingredients of laying hens fed contains lutein, zeaxanthin, which are the main xanthophylls in egg yolks (NRC, 1994). Shin et al (2015) reported that maize contained a high amount of lutein (2,096 μg/100g). Minatel et al (2014) reported that rice contained amount of lutein (243.7 μg/100g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maize is one of the most important ingredients of laying hens fed contains lutein, zeaxanthin, which are the main xanthophylls in egg yolks (NRC, 1994). Shin et al (2015) reported that maize contained a high amount of lutein (2,096 μg/100g). Minatel et al (2014) reported that rice contained amount of lutein (243.7 μg/100g).…”
Section: Resultsmentioning
confidence: 99%
“…Minatel et al (2014) reported that rice contained amount of lutein (243.7 μg/100g). Pigmentation of egg yolks is influenced mostly by layer diet (Colin et al, 2004) and maize is a rich source of xanthophylls (Shin et al, 2015). Natural xanthophylls is well-absorbed by hen intestinal cells (Gouveia et al, 1996) and is transferred to the yolk (Donald and William, 2002) after being released into the circulatory system (Salma et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The extent of yellowness in egg yolk color is known to be largely dependent on the concentration and type of dietary colorants (e.g., xanthophyll) [35,36]. Therefore, our observation for decreased egg yolk color by feeding diets containing supplemental fat is likely a consequence of replacing corn grains and corn gluten meal, which contain high amounts of egg yolk colorants, with supplemental fat.…”
Section: Discussionmentioning
confidence: 96%
“…Detailed procedures for data collection of productive performance and egg quality have been demonstrated previously [ 14 , 15 ]. In short, laying performance including hen-d egg production, egg weight, egg mass, and soft and broken egg production was recorded daily, whereas feed intake and feed conversion ratio (FCR) were recorded weekly.…”
Section: Methodsmentioning
confidence: 99%
“…Egg quality was measured with four eggs randomly collected from each replicate at the end of the experiment [ 15 ]. Eggshell color was determined using the eggshell color fan (Samyangsa, Kangwon-do, Republic of Korea; 15 = very dark brown and 1 = very light and pale).…”
Section: Methodsmentioning
confidence: 99%